Central African Economic and Monetary Community : Common Policies in Support of Member Countries Reform Programs-Press Release, Staff Report, and Statement by the Executive Director for the Central African Economic and Monetary Community. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2022)
Despite a more favorable external environment, marked by the rebound in global growth, fast-increasing oil prices, and unprecedented Fund financial support, CEMAC is ending 2021 in a fragile external position. Net external reserves fell throughout 2021 to reach their lowest level in decades, and gross reserves are just above three months of imports of goods and services. The launch of a second phase of the regional strategy at the August 2021 CEMAC Heads of States summit saw renewed commitments to accelerate structural, transparency, and governance reforms. The resumption of program engagements with the Fund, combined with high oil prices and significant fiscal adjustments in 2022, should allow for a turnaround, and the build-up in external reserves is expected to resume in 2022. Risks include possible adverse pandemic developments, oil price volatility, possible fiscal slippages, shortfall in external financing, and security issues.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet